Best Siting for Small Hill Reservoirs and the Challenge of Sedimentation: A Case Study in the Umbria Region (Central Italy) - Lorenzo Vergni; Nicola Pasquini; Francesca Todisco (Land)
This study presents a GIS-based Weighted Overlay Process (WOP) for Small Hill Reservoir Best Siting (SHRBS) in the Umbria region (central Italy), with a focus on supporting regional-scale planning rather than site-specific engineering design. The WOP incorporated commonly adopted SHRBS criteria, with suitability scores defined through two approaches: Model A, based on scoring scales from the literature, and Model B, which assigns scores based on the frequency distribution of the various attributes observed in a database of over 3000 existing SHRs in the region. The comparison between the models revealed significant differences, particularly in the scores assigned to texture, precipitation, and contributing area. Models A and B, tested on the existing SHRs, indicated quite different average suitability values (2.68 and 3.30, respectively, on a 5-point scale) and only a slight agreement (weighted Cohen’s kappa Kw ≤ 0.13). Both models also showed poor agreement (Kw < 0) when compared with a third suitability model based solely on sedimentation risk, which was developed using the Sediment Delivery Ratio from the InVEST suite. This indicates that many sites considered highly suitable by models A and B were also highly susceptible to sedimentation. Given the economic and environmental implications of sedimentation, this study recommends explicitly incorporating sedimentation risk criteria into SHRBS methodologies to enhance the effectiveness of siting decisions.